2020
DOI: 10.1111/jfpp.14631
|View full text |Cite
|
Sign up to set email alerts
|

Gravading process of Nile tilapia ( Oreochromis niloticus ) and evaluation of its biochemical and sensory changes during refrigerated storage

Abstract: Gravads were prepared from Nile tilapia (Oreochromis niloticus) and evaluated its shelf life during chilled (6°C) and iced (0°C) storage. For standardizing the gravading process, different salt:sugar combinations of gravad mix and two steaks to gravad mixture ratio (1:0.1 and 1:0.2) were selected. Gravads prepared using 1:2 salt‐sugar in the gravad mix and a ratio of 1:0.1 steaks to gravad mix was found optimum combination. Gravads prepared using the standardized combination of salt and sugar were stored at 0°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The figure shows that the initial values were 22.13 ± 1.29 and 22.82 ± 1.70 mg N/100 g of muscle for the fillets with the extract and the control, respectively. These values are similar to the 26.2 ± 1.6 mg N/100 g reported by Montoya-Camacho et al [25] and are higher than the 6.5 and 10.2 mg N/100 g for tilapia (Oreochromis niloticus) muscle described by Liu et al [34] and Pankyamma et al [54], respectively. Regarding storage time, a significant increase (p < 0.05) in TVB-N values was observed, reaching up to 34.76 ± 10.60 and 60.21 ± 10.56 mg N/100 g in the tilapia fillets with NGE and the control at day 18, respectively.…”
Section: Total Volatile Bases (Tvb-n)supporting
confidence: 88%
“…The figure shows that the initial values were 22.13 ± 1.29 and 22.82 ± 1.70 mg N/100 g of muscle for the fillets with the extract and the control, respectively. These values are similar to the 26.2 ± 1.6 mg N/100 g reported by Montoya-Camacho et al [25] and are higher than the 6.5 and 10.2 mg N/100 g for tilapia (Oreochromis niloticus) muscle described by Liu et al [34] and Pankyamma et al [54], respectively. Regarding storage time, a significant increase (p < 0.05) in TVB-N values was observed, reaching up to 34.76 ± 10.60 and 60.21 ± 10.56 mg N/100 g in the tilapia fillets with NGE and the control at day 18, respectively.…”
Section: Total Volatile Bases (Tvb-n)supporting
confidence: 88%
“…On the other hand, the determination of TVB-N is one of the most commonly used tests to measure the deterioration of fish products. Figure 3 illustrates an initial TVB-N value of 26.2 ± 1.6 mg N/100 g, greater than the 10.2 and 6.5 mg N/100 g described by Pankyamma et al (2020) and Liu et al (2010), respectively, for tilapia (Oreochromis niloticus) muscle.…”
Section: K Valuementioning
confidence: 59%
“…Sea urchins are highly nutritious and flavorful seafoods, but complex lipid composition and susceptibility to hydrolysis and oxidation lead to short shelf life and excessive quality loss during the marketing process. [ 23,24 ] After 3 days of storage at 4°C, the total lipid content and the PL content of SUG decreased, confirming that degradation of sea urchin gonadal lipids occurs during storage, which was mainly caused by the degradation of PL in the lipids. [ 25 ] Similar results showed that TAG and polar lipid (PoL) in the lipid of mussel scallop were degraded and PL as the main component of PoL was closely related to the hydrolysis of aquatic products.…”
Section: Discussionmentioning
confidence: 87%